From family to classroom: mediating roles in promoting social and emotional learning among early adolescents - Thiamta, Pantipa; Damrongpanit, Suntonrapot (International Journal of Evaluation and Research in Education (IJERE), 2025)
This research aims to examine the influence of authoritative parenting (PAREN), cooperative learning (COOP), school environment (ENVI), positive classroom climate (CLASS), and extrovert personality (EXTRO) on social and emotional learning (SEL), as well as analyze the complexity of mediating variable roles linking these factors. The sample consisted of 684 lower secondary school students from the upper northern region of Thailand. Questionnaires were used for data collection, and analysis was conducted using partial least square structural equation modeling (PLS-SEM) technique. Research findings revealed complex structures among factors collectively explaining 67.37% of SEL variance. PAREN emerged as the most powerful driving force followed by school factors, namely COOP and CLASS, which demonstrated strong interconnection while ENVI showed only indirect influence through EXTRO. Furthermore, CLASS and EXTRO functioned as significant mediating variables between classroom factors and SEL. However, EXTRO did not play a mediating role in the relationship between parenting and SEL, reflecting that family influence remains the primary factor determining SEL development in Thai youth.